Kirigami-inspired deployable mechanisms with a type-preserving feature and controllable Poisson’s ratio - Wang, Jianzhi; Xiao, Hang; Ding, Xilun; Lyu, Shengnan (Frontiers in Mechanical Engineering, 2023)
A spatial deployable mechanism is capable of adapting to different operating requirements by adjusting its shape and size. However, most current deployable mechanisms fail to maintain the type of their reflective surface during the folding process, which limits their ability to adjust the optimal operating frequency. To address this issue, this paper presents a novel design of a deployable mechanism with a type-preserving feature inspired by kirigami techniques. By preserving the type of its reflective surface, this mechanism allows for the adjustment of the optimum operating frequency according to specific requirements. This makes it well-suited for deployment on commercial satellites that undergo constant mission variations. The mechanism is constructed using porous kirigami cells, ensuring that the type of the working surface is maintained throughout the deployment process. The construction of deployable units and networks based on porous cells is also discussed. Additionally, deployable mechanisms with controllable Poisson’s ratios are developed. The kinematics of the mechanism are analyzed to verify the type-preserving characteristics. Finally, four case studies are conducted to illustrate and validate the proposed design and analysis.